Experiences of Youth Studying Together with Classmates with Special Educational Needs and Disabilities - Asakavičiūtė, Vaida; Grincevičienė, Vilija; Targamadzė, Vilija; Sederevičiūtė-Pačiauskienė, Živilė (Journal of Education Culture and Society, 2024)
Aim. Most children and young people do not have a social experience of dealing with peers with disabilities and disadvantages which causes various problems for both sides. The relevant reactions of the class group to the behaviour of a classmate with learning disabilities can have the same positive effect on the individual as the professional help of the class teacher or psychologist. The study research question was to understand how classmates perceive their experiences communicating and cooperating with peers with special educational needs or disabilities. Methods. The phenomenographic research approach was chosen to carry out the study. Face-to-face in-depth interviews were carried out to collect the data. The informant‘s selection criteria were students who had studied for at least one year in a standard classroom with peers with special educational needs or disabilities and had been in contact with and cooperated with them in general education secondary school. Results. The positive experience is related to the development of will and character traits, lessons of tolerance, development of empathy, building social support skills, and lessons in sociability. The negative experience is related to dealing with outbreaks of aggression and egression, communication problems and mistakes, and disturbances during lessons. Conclusion. The participants’ positive experiences show that the social environment and education accelerate the formation of the personality and direct it towards sociability. Participants’ negative experiences signalled the abundance of problems existing in the reality of education and their multifacetedness.